2016
DOI: 10.35790/ecl.4.2.2016.14567
|View full text |Cite
|
Sign up to set email alerts
|

Profil 10 besar kasus di Instalasi Gawat Darurat Bedah RSUP Prof. Dr. R. D. Kandou periode Januari – Desember 2015

Abstract: Emergency cases, especially in surgery field, are still a major problem globally, therefore, health centers have to provide a better preparation to face such cases. This was a retrospective descriptive study. This study was aimed to obtain the profile of the 10 major cases in emergency department of surgery from January to December 2015 at Prof Dr. R. D. Kandou General Hospital. The results showed that the case distribution was predominated by non-traumatic case (70.13%), males (64.45%), and age group of 45-64… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
1
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 1 publication
2
1
0
5
Order By: Relevance
“…The majority of patients attending hospital emergency departments had general medical problems (63%), and only 15.2% reported life-threatening conditions such as trauma and cardiovascular diseases. Similar results were found in a study on ED attendance in an Indonesian hospital; using 2015 data, roughly 70% of patients were categorised as non-trauma cases [34]. Studies have found that a significant number of patients attending hospital emergency departments had nonemergency conditions [35].…”
Section: Discussionsupporting
confidence: 80%
“…The majority of patients attending hospital emergency departments had general medical problems (63%), and only 15.2% reported life-threatening conditions such as trauma and cardiovascular diseases. Similar results were found in a study on ED attendance in an Indonesian hospital; using 2015 data, roughly 70% of patients were categorised as non-trauma cases [34]. Studies have found that a significant number of patients attending hospital emergency departments had nonemergency conditions [35].…”
Section: Discussionsupporting
confidence: 80%
“…Emergency Department as the main actor in the initial assessment of emergency cases, resuscitation and stabilization in the hope that it can reduce mortality and disability. The most handled cases in the emergency room are non-trauma cases and trauma cases, but in Indonesia trauma cases are the most frequently found cases in the emergency room (Takaendengan, Wowiling, & Wagiu, 2016). This is similar to the medical records of the Emergency Hospital Installation of Hasan Sadikin Hospital in 2016, which showed that the most common cases were trauma cases of 2644 cases.…”
Section: Introductionsupporting
confidence: 76%
“…Selain itu, terdapat rumah sakit swasta yang melayani pembedahan. [3][4][5] Di Indonesia, data kasus yang memerlukan intervensi bedah belum terangkum sepenuhnya dan dipengaruhi oleh berbagai faktor antara lain lingkungan, teknologi, dan budaya masyarakat. Unsur-unsur lain yang dapat berpengaruh berupa masalah pendanaan dan teknik pengumpulan data.…”
Section: Pendahuluanunclassified
“…Unsur-unsur lain yang dapat berpengaruh berupa masalah pendanaan dan teknik pengumpulan data. 5 Salah satu faktor yang dapat mempersulit pengumpulan data adalah luas daerah Indonesia dan jumlah pusat kesehatan yang tersebar di berbagai daerah yang belum ditunjang dengan fasilitas memadai. 6 rmin Dunia Kedokteran is licensed under a Creative Commons Attribution-NonCommercial 4.0 International Licens Ce e. Di Indonesia, kasus trauma tercatat menduduki peringkat pertama kasus bedah dan termasuk sepuluh besar kasus (bedah dan non-bedah), baik yang membutuhkan rawat inap maupun rawat jalan.…”
Section: Pendahuluanunclassified